Impacts of the delay in construction of a large scale hydropower project on potential displacees. Issue 1 (2nd January 2017) - Koirala, Sanju; Hill, Douglas; Morgan, Richard
Abstract: Literature on impact assessment and involuntary displacement mostly explains the impacts that might occur or have occurred on the local communities during and after involuntary displacement induced by development projects. However, there is only very limited research that considers the impacts local communities experience during the pre-implementation phase of the project. Our research attempts to highlight the impacts caused by large-scale projects trapped in a long pre-implementation phase and it seeks to explain the factors that intensify the impacts on affected communities. The research is based on a case study analysis of the West Seti Hydropower Project, a proposed dam in Far-Western Nepal. We argue that an adequate understanding of the impacts that occur during the pre-implementation phase of large-scale development projects is crucial to addressing problems related to displacement and resettlement. Since most of the problems of involuntary displacement begin during the pre-implementation phase, if this phase is not properly understood and its issues addressed, there will be long-term impacts on people, community and overall development processes.